Review of the genus Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae) of Western Palaearctic region - Shavrin, Alexey V. (Zootaxa, 2024)
Taxonomic and faunistic data for seven species of the atrocephalum and two species of the fusculum groups of the genus Anthobium Leach, 1819 of the Western Palaearctic region are presented. Three species are redescribed and illustrated: North African A. longicorne (Fauvel, 1886), Iberian A. moczarskii (Scheerpeltz, 1961) and Caucasian A. tenue (Eppelsheim, 1881). Five new synonymies are proposed: A. atrocephalum (Gyllenhal, 1827) = Lathrimaeum gracilicorne Luze, 1905 syn. n., = L. abantense Fagel, 1968 syn. n., = L. urgelense Fagel, 1968 syn. n., A. melanocephalum (Illiger, 1794) = L. hamatum Luze, 1905 syn. n., and A. unicolor (Marsham, 1802) = L. deinekini Roubal, 1913 syn. n. Lectotypes for Lathrimaeum deinekini Roubal, 1913, L. longicorne Fauvel, 1886 and L. tenue Eppelsheim, 1881 are designated. The habitus and aedeagi of A. atrocephalum, A. ganglbaueri (Luze, 1905), A. metallicum (Luze, 1905) and A. unicolor are provided. Aedeagi of A. longicorne, A. metallicum and A. moczarskii are illustrated for the first time. A key of Western Palaearctic species of Anthobium is presented. Distributional maps of all redescribed species are given. Several species are recorded for the first time: A. atrocephalum from Morocco, Azerbaijan and Iran, A. melanocephalum from Azerbaijan, A. moczarskii from Portugal, A. tenue from Russia, and A. unicolor and A. ganglbaueri (Luze, 1905) from Georgia.